NINE PARTS OF SPEECH IN TEACHING ENGLISH TO ELECTRICAL ENGINEERING STUDENTS - Naely Muchtar (Proceedings Education and Language International Conference, 2017)
AbstractPrior to the ASEAN Economic Community, one of the specific soft skills to be mastered for Indonesian engineers to be stand out from the other engineers of other ASEAN countries is mastering English language skills. Engineering students’ backgrounds are mostly from Vocational High School with a variety of English skills. It is quite complicated for the lecturer in teaching English for Engineering as English for Specific Purpose (ESP) subject with students’ various level of English skills. English is taught based on the Electrical Engineering content which made the lecturer’s need to analyze the students’ skill in basic words of English. This paper aims at presenting and offering the importance of teaching English through nine parts of speech which consists of noun, pronoun, adjective, verb, adverb, preposition, conjunction, and interjection, as the fundamental words of English. By mastering nine parts of speech, engineering students will easily conduct sentences into paragraph, reading English text, listening while watching tutorial video, and speaking for presenting their idea. Nine parts of speech are very practical for teaching ESP.Keywords: Parts of speech, English for engineering